Seroprevalence Of Contagious Caprine Pleuropneumonia In Small Ruminants In Maharashtra - Suryawanshi, S.N.; Tembhurne, P.A.; Gohain, S.; Kesharkar, J.A.; Tumlam, U.M.; Ingle, V.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
To study the seroprevalence of contagious caprine pleuro pneumonia (CCPP) in small ruminants in Maharashtra, a total of 165 (sheep-81 and goat-84) serum samples were collected from apparently healthy sheep and goats respectively of different age and sex from Nasik and Nagpur districts of Maharashtra. All the samples were screened for CCPP antibodies by slide agglutination test using colored CCPP antigen. An overall prevalence of 16.05 per cent and 20.24 per cent was observed in sheep and goats respectively. District wise highest prevalence of CCPP was observed (22.50 per cent) and (25 per cent) in sheep and goat respectively from Nashik. Age wise seroprevalence of CCPP in sheep and goats indicated higher prevalence of 25 per cent and 23.08 per cent, in 2-3 years age group. However, sex wise seroprevalence of CCPP was recorded highest (sheep-25 per cent and goat-35.71 per cent) in males than in females (sheep-15.07 per cent and goat-17.14 per cent) The present finding indicates endemicity of the infection in various areas of Maharashtra State.